(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Our day-to-day life has always been influenced by what people think. Ideas and opinions of others have always affected our own opinions. A vital part of the information era has been to find out the opinions of other people. In the pre-web era, it was customary for an individual to ask his or her friends and relatives for opinions before making a decision. Organizations conducted opinion polls, surveys to understand the sentiment and opinion of the general public towards its products or services. In the past few years, web documents are receiving great attention as a new medium that describes individual experiences and opinions. The explosion of Web 2.0 has led to increased activity in Podcasting, Blogging, and Tagging, Contributing to RSS, Social Bookmarking, and Social Networking. As a result there has been an eruption of interest in people to mine these vast resources of data for opinions. The enormous amount of heterogeneous data that is generated by the users of these communities, offers an unprecedented opportunity to create and employ theories & technologies that search and retrieve relevant data from the huge quantity of information available and mine for opinions thereafter. Sentiment Analysis or Opinion Mining is the computational treatment of opinions, sentiments and subjectivity of text. Keywords- Sentiment Analysis, Tasks , and Levels, Web2.0.